1995
DOI: 10.1126/science.268.5213.1019
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic Ray and Solar Particle Investigations Over the South Polar Regions of the Sun

Abstract: Observations of galactic cosmic radiation and anomalous component nuclei with charged particle sensors on the Ulysses spacecraft showed that heliospheric magnetic field structure over the south solar pole does not permit substantially more direct access to the local interstellar cosmic ray spectrum than is possible in the equatorial zone. Fluxes of galactic cosmic rays and the anomalous component increased as a result of latitude gradients by less than 50% from the equator to -80 degrees . Thus, the modulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…(This effect is visible most clearly in the integral intensity trace for the slow latitude scan in Fig. 2d; see Simpson et al, 1995 for a fuller discussion.) At the same time, periodic enhancements of low energy particles accelerated by the shocks bounding the CIRs were also observed.…”
Section: Latitudinal Structure Of Solar Modulation Of Cosmic Raysmentioning
confidence: 92%
See 1 more Smart Citation
“…(This effect is visible most clearly in the integral intensity trace for the slow latitude scan in Fig. 2d; see Simpson et al, 1995 for a fuller discussion.) At the same time, periodic enhancements of low energy particles accelerated by the shocks bounding the CIRs were also observed.…”
Section: Latitudinal Structure Of Solar Modulation Of Cosmic Raysmentioning
confidence: 92%
“…1, and no effect at all was detectable for the low energy galactic cosmic rays (panel c). Together with other evidence, such as observations near the poles of periodic variations in the intensity of high energy cosmic rays (McKibben et al, 1995;Kunow et al, 1995;Simpson et al, 1995) and of low energy interplanetary accelerated particles produced by near-equatorial solar wind stream corotating interaction regions (CIRs) (Sanderson et al, 1995;Roelof et al, 1996), the observations led to the conclusion that transport of energetic charged particles across the mean interplanetary magnetic field between the equatorial and polar regions was much more efficient than existing models had contemplated (e.g. Fisk, 1996;Kóta and Jokipii, 1998;McKibben, 1998;Potgeiter, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…During solar minimum, except near apogee in its orbit, Ulysses will neither measure particles in the near‐ecliptic current sheet nor the effects of the current sheet in accelerating particles (including at corotating interactions regions (CIRs)). Above the heliosphere current sheet, the fluxes of particles are measured to be very low [e.g., Lanzerotti et al , 1995; Simpson et al , 1995]. However, this solar minimum limitation in the statistics is not a serious limitation of this study in that the solar maximum fluxes (which become the particle reservoirs) are of sufficient intensity to be the dominant player when determining the longer‐term implications of the heliosphere radiation environment beyond Earth orbit.…”
Section: Introductionmentioning
confidence: 94%
“…In a Fisk-type field, magnetic field lines exhibit extensive excursions in heliographic latitude, and this has been cited as a possible explanation for recurrent energetic particle events observed by the Ulysses spacecraft at high latitudes (see, e.g., Simpson et al 1995;Zhang 1997;Paizis et al 1999), as well as the smaller than expected cosmic-ray intensities observed at high latitudes (Simpson et al 1996). The Fisk field and the physics behind it have been discussed in a series of papers (see, e.g., Fisk & Schwadron 2001, and references therein) where it is assumed that the polar coronal hole is symmetric with respect to the solar magnetic axis, and that the magnetic field expands nonradially.…”
Section: The Heliospheric Magnetic Fieldmentioning
confidence: 99%